The role of administrative courts in shaping the development directions of the sustainable development principle: remarks regarding case-law in environmental protection and spatial planning cases - Jaśkiewicz-Kamińska, Sylwia (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: This text presents the results of the process of juridization of the sustainable development principle in international, EU and national law, as well as the development of that principle with regard to the application of law practice. Aim: At the same time, the text attempts to define the role of an administrative court as a body reinterpreting the sustainable development principle in environmental protection and spatial planning cases, bearing in mind both the ecological as well as social justice outlook Results: As a result, the study presented focuses on determining the impact of the administrative courts’ established case-law on the application of the sustainable development principle by national public administration authorities.